Investigation of Satellite Trace (ST) and Multi-reflected Echo (MRE) ionogram signatures and its possible correlation to nighttime spread F development from Cyprus over the solar mini-max (2009–2016). Issue 6 (15th March 2021) - Paul, K.S.; Haralambous, H.; Oikonomou, C.; Paul, A.
Abstract: Multi-reflected echoes (MREs) and satellite traces (STs) are referred in literature as ionogram signatures of Travelling Ionospheric Disturbances (TIDs) which is a phenomenon that apparently drives spread F development mainly at nighttime mid-latitude ionosphere. A long-term statistical study has been undertaken to investigate the morphological aspect of these signatures over the lower midlatitude European station of Nicosia, Cyprus (35.19°N, 33.38°E geographic; magnetic dip. 29.38°N) by inspecting all ionograms recorded by the DPS-4D digisonde in the interval 2009–2016. The results underline the systematic manifestation of these TID signatures over Cyprus with a possible (although not quite clear) solar activity dependence and a distinctive seasonal and diurnal occurrence rate with a seasonal peak of STs during summer and of MREs during January to April. Based on the experimental results of the present study, the seasonal occurrence rate of MREs and STs is found to increase by 75% and 56% during high solar activity periods. Satellite traces are well known ionogram signatures of TIDs and mostly correlated to the nighttime spread F formation. The occurrence of mid-latitude spread Fs over European longitude sector normally increases during summer. The occurrences of TIDs are also prominent at this interval of the year over nighttime mid-latitude ionosphere. The presence of MREs as an ionogram signature of TIDs over mid-latitude ionosphere is unique in nature.